2011
DOI: 10.1007/s11665-010-9790-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cyclic Loading on the Uniaxial Behavior of Nitinol

Abstract: The widespread development and use of implants made from NiTi is accompanied by the publication of many NiTi material characterization studies. These publications have increased significantly the knowledge about the mechanical properties of NiTi. However, this knowledge also increased the complexity of the numerical simulation of NiTi implants or devices. This study is focused on the uniaxial behavior of NiTi tubing due to cyclic loading and had the goal to deliver both precise and application-oriented results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…While numerous computational (Grujicic et al, 2012;Kumar et al, 2013;Rebelo et al, 2009) and some experimental studies (Pelton, 2011;Pelton et al, 2008) of device-level fatigue have incorporated crimping and deployment into the investigational protocol, few studies have clearly examined how this pre-strain cycle impacts overall fatigue properties. Schlun et al subjected pseudoelastic NiTi to an 8% tensile pre-strain and examined the evolution of the cyclic strain-stress behavior at 0.2% and 1.2% strain amplitude and 2% mean strain for 100 cycles (Schlun et al, 2011). The authors observed hysteresis and permanent set in the stress-strain curve at 1.2% strain amplitude over 100 cycles but the curve remained constant at 0.2% strain amplitude.…”
Section: Introductionmentioning
confidence: 99%
“…While numerous computational (Grujicic et al, 2012;Kumar et al, 2013;Rebelo et al, 2009) and some experimental studies (Pelton, 2011;Pelton et al, 2008) of device-level fatigue have incorporated crimping and deployment into the investigational protocol, few studies have clearly examined how this pre-strain cycle impacts overall fatigue properties. Schlun et al subjected pseudoelastic NiTi to an 8% tensile pre-strain and examined the evolution of the cyclic strain-stress behavior at 0.2% and 1.2% strain amplitude and 2% mean strain for 100 cycles (Schlun et al, 2011). The authors observed hysteresis and permanent set in the stress-strain curve at 1.2% strain amplitude over 100 cycles but the curve remained constant at 0.2% strain amplitude.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that annealing the alloy above the recrystallization temperature (600°C) reduces the maximum recovery stress significantly. M. Schlun et al [5] studied the uniaxial behavior of Nitinol tubing due to cyclic loading. Their study showed that a pre-straining level >6% will alter the plateau stresses.…”
mentioning
confidence: 99%